ANALISIS PENGARUH TENAGA KERJA, MODAL DAN BAHAN BAKU TERHADAP HASIL PRODUKSI HOME INDUSTRI TELUR ASIN DI DESA KEBONSARI KECAMATAN CANDI KABUPATEN SIDOARJO - Aliya, Nilam Nur; Priyono, Joko (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2021)
Sidoarjo Regency has many economic sectors, both in the micro sector and in the macro sector. The macro economy is realized by the existence of industries or factories, while the micro economy is manifested by Small and Medium Enterprises (UKM) in the form of small industries or home industries. Sidoarjo Regency has many household business sectors such as Salted Eggs in Kebonsari Village, Candi District. The development of the salted egg industry in Kebonsari Village has been late in improving the economy of the surrounding community.The research method uses quantitative methods by going directly to the field. The analysis method used in this research is multiple linear regression, f test, and t test. The results of data analysis show that simultaneously the variables of labor, capital and raw materials have an effect on the production of salted egg industry in Kebonsari Village, Candi District, Sidoarjo Regency. Partially the labor variable has no effect and is significant on the yield of salted egg industrial houses, while the variables of capital and raw materials have a significant and significant effect on the production of the written batik industry in salted eggs in Kebonsari Village, Candi District, Sidoarjo Regency. The value of R square (R²) is 0.596, this means that the variables of labor (X1), capital (X2) and raw materials (X3) have the power to produce results (Y) of 59.6%, while the remaining variables are 30, 4% evidence by other variables outside of this study